2016
DOI: 10.1128/aac.01365-16
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of NDM-5- and MCR-1-Producing Escherichia coli Clones ST648 and ST156 from a Single Muscovy Duck (Cairina moschata)

Abstract: c Two Escherichia coli clones (sequence type 648 [ST648] and ST156) that coproduce NDM-5 and MCR-1 were detected from a single fowl in China. The bla NDM-5 gene was found on the two indistinguishable IncX3 plasmids from the two different E. coli isolates, whereas the mcr-1 gene was located on IncHI2 and IncI2 plasmids, respectively, suggesting that bla NDM-5 and mcr-1 have spread in avian intestinal flora. Also, the two strains harbor bla TEM-1 , bla CTX-M-55 , fosA3, and aac(6=)-Ib. The multiresistant E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
87
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 27 publications
8
87
1
Order By: Relevance
“…The mcr -1-producing isolates in this study were belonged to phylogenetic groups A and B1, which were mainly distributed among human commensal E. coli isolates [23]. The mcr -1 producing isolates were assigned by MLST to two different sequence types: ST156 and ST167 (Table 1), which was similar to previous reports in other studies from China [8, 22]. E. coli ST156 has been found that it has connection with different ESBL genes [24, 25].…”
Section: Resultssupporting
confidence: 86%
“…The mcr -1-producing isolates in this study were belonged to phylogenetic groups A and B1, which were mainly distributed among human commensal E. coli isolates [23]. The mcr -1 producing isolates were assigned by MLST to two different sequence types: ST156 and ST167 (Table 1), which was similar to previous reports in other studies from China [8, 22]. E. coli ST156 has been found that it has connection with different ESBL genes [24, 25].…”
Section: Resultssupporting
confidence: 86%
“…The emergence of carbapenem-and colistin-resistance determinants in single strains ushers in a new age of pandrug resistance, and underscores the rapid depletion of our antimicrobial armamentarium (Delgado-Blas, Ovejero, Abadia-Patino, & Gonzalez-Zorn, 2016;He et al, 2017;Sun et al, 2016;Yang et al, 2016). The detection of plasmids harboring both carbapenem and colistin resistance genes has made colistin resistance, which was hitherto solely mediated by mutations in and insertional inactivation of phoPQ, ccrB, mgrB, pmrAB, lpxACD, and pmrHFIJKLM, and restricted to chromosomal or vertical transmission, a grave threat to clinical medicine (Beceiro et al, 2014;Cannatelli et al, 2014;Giani et al, 2015;Jayol, Nordmann, Brink, et al, 2017;Jayol, Nordmann, Lehours, Poirel, & Dubois, 2017;Mavroidi et al, 2015;Wright et al, 2015).…”
mentioning
confidence: 99%
“…In the two years since its first discovery in Southern China, in late of 2015 [15], mcr-1 has been detected to coexist with bla NDM-1 -like genes in migratory birds (like the Muscovy duck [16] plus chickens [17]), in healthy people [18] and also in patients with bloodstream infections [6,7,9,19]. This indicates that the possible route of mcr-1 / bla NDM -like genes is through the food-chain transmission.…”
mentioning
confidence: 99%
“…This indicates that the possible route of mcr-1 / bla NDM -like genes is through the food-chain transmission. With the exception of Cronobacter sakazakii that carries NDM-9 [20], E. coli seems to be the predominant reservoir for the coexistence of MCR-1 and NDM-like enzymes [69,16–19,21,22]. Surprisingly, mcr-3 , a new mcr -like gene, was found in an XDR- E. coli clinical isolate which harbored both mcr-1 and bla NDM-5 [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation